Assessing wheat (Triticum aestivum) genotypes for Yr resistance genes using conserved regions and simple-sequence motifs - (:unkn) unknown (FUNPEC-EDITORA, 2011)
Analysis of DNA sequence variation among genotypes is useful for differentiation of wheat accessions, selection strategies and genetic development of crop plants. We screened molecular markers for yellow rust resistance genes (Yr7, Yr9, Yr15, Yr18, Yr26, and YrH52), which are in the gene-rich regions of wheat chromosomes 1B, 2B, and 7D, to investigate DNA sequence differences and repeat motifs and numbers between wheat cultivars resistant (Izgi2001, Sonmez2001, PI178383) and susceptible (Aytin98, ES14, Harmankaya99) to yellow rust. The F-2 individuals derived from the crosses were evaluated for yellow rust resistance at both the seedling and adult stages to identify DNA markers genetically linked to yellow rust resistance. The most repeated motif was found to be GA and the least repeated motif TAGA among the cultivars. When we examined DNA sequence differences (insertion, deletion and single nucleotide changes), the molecular markers Xgwm526 (Yr7) and Xgwm273 (YrH52) were found to have the most conserved regions and Yr15 (Xgwm413) the least conserved regions among the cultivars. This DNA sequence information can be used for selection of suitable parents, creating mapping populations and developing molecular markers associated with yellow rust resistance in plant breeding programs.
Keywords: DNA sequence; Gene-rich region; Molecular marker; Resistance; Yellow rust; MICROSATELLITE MARKERS; DNA; ABUNDANCE; POLYMORPHISMS; DIVERSITY; BARLEY; IDENTIFICATION; REPEATS; RICE; TAGS